PERANCANGAN SISTEM INFORMASI MONITORING INSTALLER PADA PT GRAHA SUMBER PRIMA ELEKTRONIK JAKARTA - Achmad Wendi; Ardiansyah Dores (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2018)
In order to devise monitoring installation, developing a function system for increase performance project department and monitoring installer job. This system has been building for make project manager job easier, according to act knowledge the progress for installation BTS (Base Transceiver Station). Also for helping  installer to do their job in the field (directly). This information system has design to take in purchase order, work order production, instruction work letter, procurement cost installation and installation monitoring. The methode is refer to waterfall method. Programe language will used for increasing software is VB.Net.Keywords:Monitoring Installation, Purchase Order, Work Order, Instruction Work Letter.